Exploiting the MIL-STD-1553 avionic data bus with an active cyber device. Issue 100 (January 2021) - De Santo, D.; Malavenda, C.S.; Romano, S.P.; Vecchio, C.
Abstract: The ensemble of cyber and electromagnetic activities has become predominant in present-day battlegrounds and armed forces are witnessing the introduction of complex and interconnected weapon systems. According to United States military doctrine, cyberspace has been classified as the fifth dimension of the battlespace and much effort is being devoted by NATO to secure activities in such an environment. This paper delves its roots in a vast research endeavor aimed at granting cyber resilience of current and future assets. Within such a broad and challenging domain, the work has a very precise scope: to address the vulnerabilities of a specific avionic platform protocol, namely the MIL-STD-1553 standard. The discussion will unfold into the design and implementation of a cyber device that is able to exploit the identified vulnerabilities. The device in question will also be tested to prove the effectiveness of the proposed solution. The outcomes will stand as a call to action towards improving the security of state-of-the-art avionic systems.